Research on system call forwarding mechanism of SGX-based LibOS - LIU Ximeng; HUANG Yingkang; LIU Weijie; FAN Beixi; ZHANG Tian; ZHANG Jie (Tongxin xuebao)
SGX-based LibOS are designed to run unmodified applications within SGX Enclave, but differences in their architecture, system call simulation, and system call forwarding can make them difficult to use and debug. To overcome these challenges, a dynamic testing framework was introduced that traced system calls and verified their behaviors in various SGX-based LibOS. This framework compared the execution of system calls within the LibOS to their execution on regular Linux hosts, analyzing the differences in call forwarding mechanisms, Linux feature replication, and runtime support for programming languages. The study aims to highlight where improvements are needed and hopefully provides guidance for future research in this area.